"If I tell you my problems, how will you perceive me?": A qualitative study of mental health knowledge, barriers, and opportunities for care among Kenyan adolescents during COVID-19. - Vincent Nyongesa; Joseph Kathono; Shillah Mwavua; Darius Nyamai; Obadia Yator; Ian Kanyanya; Nabila Amin; Simon Njuguna; Jill Ahs; Brandon Kohrt; Bruce Chorpita; Beatrice Madeghe; et al. (PLoS ONE)
Introduction The majority of the world's adolescents live in low-and middle-income countries (LMICs). However, there is a dearth of knowledge about adolescents' perspectives on mental health and sources of distress there. Therefore, a qualitative study of adolescents' and caregivers' beliefs and experiences related to mental illness was conducted in Nairobi, Kenya. Materials and methods Six focus group discussions were conducted with 46 participants at two peri-urban settlements in Nairobi from November to December 2020. Using a two-step analytic process, we generated core themes, and the study team reviewed the transcripts and triangulated the themes. Results Themes include knowledge about mental health and illness, triggers of psychological disturbances, attitudes towards mental illness, practices adopted to strengthen mental health, barriers to strengthening mental health among young people, emerging needs around caregiver mental health and parenting, and community recommendations on interventions. Adolescents had limited knowledge of specific mental illnesses but articulated triggers, stresses, and challenges they face in daily life in an in-depth manner. Caregivers demonstrated a breadth of knowledge and understanding of adolescent mental health. Conclusion Adolescents and their caregivers face tremendous stresses in the Nairobi settlements. Mental health literacy is limited, but adolescents and caregivers are ready to embrace mental health services. Reducing stigma and access to youth-friendly services are crucial to expanding service engagement.